INOVASI DESAIN DALAM MEWUJUDKAN KELAYAKAN LINGKUNGAN PERUMAHAN DAN PASAR PADAT TEPI SUNGAI KOTA, STUDI KASUS : LINGKUNGAN PASAR ASTANA ANYAR, PUSAT KOTA BANDUNG - Kusliansjah, Yohanes Karyadi; Priyanti, Eva (Ide dan Dialog Desain Indonesia (Idealog), 2017)
The emergence of spilled markets and dense residential neighborhoods on the river banks in AstanaAnyar, is one of the impacts that caused by land crisis phenomenon occurred in the city center of Bandung. AstanaAnyar market and dense housing conditions fueled the emergence of a slum environment. Standing between tworivers and low land contours causes Astana Anyar market and the surrounding housing environment have a hugethreat of flooding due to river floods during heavy rains and exacerbate existing environmental conditions.Standing in the city center of Bandung, Astana Anyar market and the surrounding housing location areahave an opportunity of building structures toward vertical buildings and development feasibility on high-valueland locations that meet market prices in the city center.Degradation of environmental conditions that occur, causing housing conditions to be unfit and unhealthyfor the community. In addition, Astana Anyar market also experienced a decline in its quality as one of theimportant economic drivers. In this condition, Astana Anyar market and the surrounding housing environmentneed an innovative solution to structuring the dense residential and market environment.By conducting direct observation and interviews to the local community and market users, this researchattemps to examine deeper about the problems and potential that exist, so that could be used as a referenceformulation of design innovation solutions that could be done as an effort to structuring the dense housing andmarket to be sustainable environment.